2018
DOI: 10.1186/s13256-018-1708-x
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of ipilimumab and nivolumab induced thyroid storm in a patient with Hashimoto’s disease and diabetes mellitus: a case report

Abstract: BackgroundRecently, immune checkpoint inhibitors have widely been used for the management of advanced melanoma. However, high-grade immune-related adverse events can occur, particularly with combination immunotherapy. We report a case of a patient with melanoma who developed thyroid storm following treatment with ipilimumab and nivolumab.Case presentationAn 85-year-old Japanese man with a history of malignant melanoma presented to our department with severe thyrotoxicosis and poor blood glucose control. He was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
(24 reference statements)
0
25
0
Order By: Relevance
“…In general, people with skin autoimmune disorders can be managed safely even in case of very severe flares (50). The same apply for those with thyroid dysfunction but severe hyperthyroidism can be encountered even in previously chronic hypothyroid patients (55).…”
Section: Discussionmentioning
confidence: 99%
“…In general, people with skin autoimmune disorders can be managed safely even in case of very severe flares (50). The same apply for those with thyroid dysfunction but severe hyperthyroidism can be encountered even in previously chronic hypothyroid patients (55).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the identification of TS tends to be delayed in patients with DKA because of suppression by fever 13,44,45 and relatively low thyroid hormone levels. 40,56 Our patient presented a high fever even after DKA was corrected, and this clinical presentation might delay the diagnosis of TS. In addition, thyroid hormones may decrease the possible compensation mechanism, leading to multi-organ dysfunction.…”
Section: Case Presentationmentioning
confidence: 84%
“…11 The literature related to TS was searched from 2016 to 2019, and the clinical characteristics of gastrointestinal symptoms in patients with TS were found to mainly be nausea, and the main cause of TS to be Graves' disease with unknown or poor compliance with anti-thyroid drugs (Table 3). [33][34][35][36][37][38][39][40][41][42][43][44][45][46] Considering that hiccups are not common in either DKA or TS, we speculate that the incidence of intractable hiccups is rare when DKA overlaps with TS. By carefully searching the literature, we found the following related cases.…”
Section: Case Presentationmentioning
confidence: 99%
“…Patients may be asymptomatic or only show non-specific symptoms, such as fatigue, dizziness, weight changes, and emotional or behavioral changes ( 18 ). Thyroid disorders are often neglected because their presentation is often inconspicuous and only a few patients have thyroid storms ( 16 ). It can also be easily deduced from the aforementioned literature that the median time from the beginning of drug commencement to the development of thyroid dysfunction varies in different immunotherapies.…”
Section: Specific Effects Of Iraes On the Thyroidmentioning
confidence: 99%
“…Thyroid dysfunction is a common pathological state of thyroid hormone disorder, most commonly hypothyroidism ( 15 ). It needs active surveillance and treatment; otherwise, severe thyroid dysfunction may seriously affect health in some cases ( 16 , 17 ). The specific mechanism of hypothyroidism is still unclear and warrants further laboratory and clinical exploration.…”
Section: Introductionmentioning
confidence: 99%